Comparing Real and Imitative Practice with No Practice during Observational Learning of Hand Motor Skills from Animations - Maliha Naushad Mian; Hannah Beder; Nadine Marcus; Paul Ayres (MDPI AG, 2024)
In two experiments, we compared the effects of practice (real and imitative) with no practice on the observational learning of hand motor skills from animated videos. Experiment 1 investigated learning to play a series of piano clips of varying complexity. Results demonstrated improved learning efficiency with imitative practice compared to no practice. Experiment 2 featured a paper-folding task, and results indicated that real practice led to significantly greater learning than no practice. Furthermore, a significant interaction was found with gender and practice, where females learned best with both real and imitative practice, but males did not benefit from these interventions. However, males outperformed females in the no practice condition. Overall, we found benefits of practice versus no practice for both tasks. However, the most effective type of practice was dependent upon the task: imitative practice for piano playing, and real practice for paper folding. Task complexity and gender were also found to be moderating factors.